Study of the heterogenous crystallization of polypropylene with various coupling agents - Ronca, Gladys; Márquez, Leni; Albano, Carmen (Rev. Téc. Fac. Ing. Univ. Zulia, 1970)
In this work the nucleating effect on the crystallization of polypropylene (PP) of certain pigments of common use, like phtalocianine and quinacridone treated or not with various coupling agents, has been studied and compared with that of talc and sodium benzoate. Such effect has been assesed by DSC, light microscopy, electron microscopy and tensile tests. It was confirmed that the increase in crystallization temperature is related to the average distance between the nuclei, been phtalocianine and quinacridone not treated those which have caused the highest shift in crystallization temperature. For those additives treated with coupling agents, no additional increase in crystallization temperature or changes in polymer morphology were observed, indicating thus that the chemical nature of the surface of the nucleating agent is not an important factor to explain their nucleating activity. The use of coupling agents has improved, to sorne extent, the mechanical properties of PP mixed with talc, followed by sodium benzoate, bul not for those mixed with phtalocianine or quinacridone.